Phylogenic Analysis and Molecular Characterization of Slemani/Kurdistan/2013 Foot and Mouth Disease Virus Shows Circulation of New Genotype in Iraq - Rashid, Peshnyar Muhammad Atta; Marouf, Ari Salahadin; Raheem, Zhino Hussen; Babashekh, Muhamad Omer (Sulaimani Journal for Pure and Applied Sciences, 2014)
Foot-and-mouth disease (FMD) is endemic in Iraq. There were no much informations about FMD genotypes in Iraq. In this study, FMD type A virus was identified by RT-PCR from a cow in Kurdistan region. Viral protein1 (VP1) was amplified, sequenced and published in National Center for Biotechnology Information (NCBI) GenBank as Slemani/Kurdistan/2013. VP1 nucleic acid and amino acid sequence of Slemani/Kurdistan/2013 was comparatively analysed with all previously published Iraqi FMDV type A sequences available in NCBI Gen Bank from 1964 to 2013. The result indicated that Slemani/Kurdistan/2013 had 10 amino acid residues in immunogenic VP1 region, which were not present in other Iraqi FMD isolates. Furthermore, sequence alignment of Slemani/Kurdistan/2013 showed the amino acid identity ranged from 83 % to 93%, and the nucleotide identity ranged from 69% to 93% with other Iraqi FMDV type A isolates. Phylogenetic tree analysis showed that the identified field isolate differed from the other Iraqi subtype and could be placed in distinct sub lineages. It can be concluded that new genotype was circulated in Iraq. Therefore, monitoring the emergence of new FMDV strains in Iraq is important to enable appropriate vaccines selection.
Keywords: FMD type A FMDV Kurdistan region phylogenic tree analysis Sulaimani